Interval Prediction of the Proportion of Dominant Wound Pathogens in the Etiological Structure of Wound Infections and Evaluation of the Potential Effectiveness of Antimicrobial Agents - S. G. Fominykh; A. I. Danilov; V. N. Gonnoshenko; E. V. Kalchenko (Антибиотики и Химиотерапия)
Monitoring of quantitative and qualitative properties ofmicroorganisms - pathogens ofwound infections - in a multidisciplinary hospital, carried out by the disco-diffusion method on a regular basis during the period from 2004 to 2018 allowed to build a short-term interval prognosis to identify the dominant pathogens. S.aureus, K.pneumoniae, P.aeruginosa, S.pyogenrs, and E.faecalis were the most important for determining the registry of potentially effective antimicrobial agents in the structure of wound pathogens. The affiliation of wound S.aureus to PRSA with a wide arsenal of possible effective agents for wound infections caused by this pathogen and a progressive decrease in the potential of cefoperazone/sulbactam and carbapenems against wound infections caused by K.pneumoniae and P.aeruginosa have been demonstrated. The feasibility of laboratory testing of the potential efficacy of cefepime/sulbactam, ceftazidime/avibactam, piperacillin/tazobactam, ticarcillin/clavulanate, netilmicin, tigecycline, and doripenem is justified. The need for vancomycin and linezolid for the treatment of patients with wound infections caused by MRSA and E.faecalis was determined.